Rubber Agriculture Tapanuli in the Malaise Era, 1929 – 1939 - Edi Sumarno; Junita Setiana Ginting; Nina Karina; M. Azis Rizky Lubis (Budapest International Research and Critics University, 2020)
Entering the early 1930s, people's purchasing power has decreased due to the sluggish world economy. This event was later called